2020
DOI: 10.1007/s11538-019-00681-2
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection, Altered Vector Infectivity, and Antibody-Dependent Enhancement: The Dengue–Zika Interplay

Abstract: Although dengue and Zika cocirculation has increased within the past 5 years, very little is known about its epidemiological consequences. To investigate the effect of dengue and Zika cocirculation on the spread of both pathogens, we create a deterministic dengue and Zika coinfection model, the first to incorporate altered infectivity of mosquitoes (due to coinfection). The model also addresses increased infectivity due to antibody-dependent enhancement (ADE) within the human population. Central to our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The presence of IgG antibodies indicated that the participants were previously infected with DENV and ZIKV, as determined by immunoblot assay serology. IgG antibodies can be detected for years or even a lifetime [ 11 ]; therefore, in the current study, we could not determine when the study participants were infected with the two flaviviruses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of IgG antibodies indicated that the participants were previously infected with DENV and ZIKV, as determined by immunoblot assay serology. IgG antibodies can be detected for years or even a lifetime [ 11 ]; therefore, in the current study, we could not determine when the study participants were infected with the two flaviviruses.…”
Section: Discussionmentioning
confidence: 98%
“…The antibody seropositivity against DEN and ZIKV was high, but almost the same across HIV-positive and HIV-negative individuals. These findings seem ambiguous, but the most valid explanation could be that most of the study participants were women, which could be attributed to the health-seeking behaviours of women and the strict adherence to antiretroviral medication among HIV-positive individuals and routine antenatal care during pregnancy [ 11 ], as most of the study participants from the three regions were recruited from the antiretroviral and antenatal units of tertiary healthcare centres.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the feasible solution of dengue-malaria model is given by 11 + } Thus, the solution of dengue-malaria model is bounded in D.…”
Section: Invariant Regionsmentioning
confidence: 99%
“…Ref. [11] proposed a co-infection of altered vector infectivity and antibody-dependent enhancement of dengue-zika interplay. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…An additional problem with flavivirus infections is represented by coinfections, not only by different viruses in the same family (e.g. DENV/ZIKV [ 8 , 9 ]), but also by different virus families (e.g. DENV/SARS-CoV-2 [ 10 , 11 ] or DENV/influenza [ 12 ]), which creates immune response disorders, confusion in diagnosis and delays in treatment, leading to additive or synergistic morbidities [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%